Improving governance learning for sustainable development: introductory reflections on a specific issue in adult education - Giovanna Del Gobbo (Firenze University Press, 2019)
Good governance is considered a pillar in the implementation of the Sustainable Development Agenda 2030. Failures in governance processes are considered to be at the origin of countless problems in ecosystem services management. The influence of formal and informal institutions, the role of state and non-state actors, the nature of multi-level interactions and the importance of social and economic conditions, that can facilitate or increase citizen participation, are identified as structural features of governance systems. The functioning of these systems is conceptualized as social learning as a conceptual framework to understand the dynamics and the adaptive capacity of governance systems to develop learning. Informal networks are considered to play a crucial role in these learning processes. This contribution presents a reflection on learning dimension of governance, based on relationships among sustainability, human development and ecosystem protection.   Apprendimento e governance per lo sviluppo sostenibile: riflessioni introduttive su un tema specifico dell'educazione degli adulti Una buona governance è considerata un pilastro nell'attuazione dell'Agenda 2030 per lo sviluppo sostenibile. I fallimenti nei processi di governance sono considerati all'origine di numerosi problemi nella gestione dei servizi ecosistemici. L'influenza delle istituzioni formali e informali, il ruolo degli attori statali e non statali, la natura delle interazioni multilivello e l'importanza delle condizioni sociali ed economiche, che possono facilitare o ostacolare la partecipazione dei cittadini, sono identificate come caratteristiche strutturali dei sistemi di governance. Il funzionamento di questi sistemi è interpretato come apprendimento sociale in un quadro concettuale volto a comprendere le dinamiche e la capacità adattativa dei sistemi di governance in termini di apprendimento. Alle reti informali è riconosciuto un ruolo cruciale in questi processi. Il presente contributo presenta una riflessione sulla dimensione dell'apprendimento nei processi di governance, basata sulle relazioni tra sostenibilità, sviluppo umano e protezione degli ecosistemi.